Rituximab Therapy for Primary Sjögren's Syndrome: An Open‐Label Clinical Trial and Mechanistic Analysis1. Issue 4 (28th March 2013) - St.Clair, E. William; Levesque, Marc C.; Prak, Eline T. Luning; Vivino, Frederick B.; Alappatt, Chacko J.; Spychala, Meagan E.; Wedgwood, Josiah; McNamara, James; Moser Sivils, Kathy L.; Fisher, Lytia; Cohen, Philip; for the Autoimmunity Centers of Excellence
Abstract Objective To study the safety and clinical efficacy of rituximab therapy for primary Sjögren's syndrome, as well as to investigate its mechanisms. Methods Patients with primary Sjögren's syndrome were enrolled in an open‐label trial, were given rituximab (1 gm) infusions on days 1 and 15, and were monitored through week 52. The primary end point was safety, with secondary end points evaluating clinical and biologic efficacy. Blood was obtained for enumeration of lymphocyte subsets, measurement of serum autoantibody and BAFF levels, and analysis of gene expression. Results Twelve female patients with primary Sjögren's syndrome were administered rituximab. They had a median age of 51 years (range 34–69 years) and a median disease duration of 8.0 years (range 2–18 years). We observed no unexpected toxicities from the rituximab therapy. Modest improvements were observed at week 26 in patient‐reported symptoms of fatigue and oral dryness, with no significant improvement in the objective measures of lacrimal and salivary gland function. The recovery of blood B cells following the nadir from rituximab therapy was characterized by a predominance of transitional B cells and a lack of memory B cells. While blood B cell depletion was associated with an increase in serum BAFF levels, no significant changes were observed in the levels of serum anti‐Ro/SSA, anti‐La/SSB, and anti–type 3 muscarinic acetylcholine receptor autoantibodies or in the blood interferon signature. Conclusion In patients with primary Sjögren's syndrome, a single treatment course of rituximab was not associated with any unexpected toxicities and led to only modest clinical benefits despite effective depletion of blood B cells.